THE INFLUENCE OF MERCHANDISE ASSORTMENT, CUSTOMER EXPERIENCE, AND SERVICE QUALITY ON REPURCHASE INTENTIONSOCIOLLA STORE - Made Astarani Krisna Putri; Putu Saroyini Piartrini (Adisam Publisher, 2025)
The growth of the beauty industry is increasing in line with the growth of the number of beauty business industries. The high competition between companies involved in the beauty sector has caused competition between cosmetic stores in Bali to be very tight. Sociolla is one of the cosmetic stores in Bali that was established in 2015 with its head office in West Jakarta. This study aims to predict merchandise assortment, customer experience, and service quality from the perspective of The Stimulus-Organism-Response Theory by considering repurchase intention. Based on survey data from 130 Sociolla consumers, the results of multiple regression analysis revealed that merchandise assortment, customer experience, and service quality have a positive effect on the repurchase intention of Sociolla consumers. The implications of this finding recommend that Sociolla management or similar companies pay attention to the factors that cause repurchase intention. Further research is suggested to test the consistency of the findings by including customer satisfaction as a moderator in the conceptual model.